If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 5x + -4 + 3x + 2x + 2 = 180 Reorder the terms: -4 + 2 + 4x + 5x + 3x + 2x = 180 Combine like terms: -4 + 2 = -2 -2 + 4x + 5x + 3x + 2x = 180 Combine like terms: 4x + 5x = 9x -2 + 9x + 3x + 2x = 180 Combine like terms: 9x + 3x = 12x -2 + 12x + 2x = 180 Combine like terms: 12x + 2x = 14x -2 + 14x = 180 Solving -2 + 14x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 14x = 180 + 2 Combine like terms: -2 + 2 = 0 0 + 14x = 180 + 2 14x = 180 + 2 Combine like terms: 180 + 2 = 182 14x = 182 Divide each side by '14'. x = 13 Simplifying x = 13
| 3-3x=-21 | | 3x+4=-2x^2 | | 0.4y^3+0.3y^3-0.2y^3= | | 5-2(n+2)+6=16 | | f(x)=2x(x+3)-2x^2-6x+5 | | 2/3h-1/3h+11=8 | | 0.4y^3+0.3y^33-0.2y^3= | | x-9/4=7 | | 120+36x=12x | | Z^3=Z^2+30Z | | 28/9=x/1.8 | | 18=16t^2 | | f(x)=2x(7x+13)-9 | | -2r^2+5r+2=0 | | 7(d-2)=(5d+2) | | y=(5x-2)(5)-3x+17 | | b+9/12=-3 | | 2(m+5)-4(m+3)=6 | | y=5x+6x^2-2(x-3) | | y+2=0.6(x+6) | | x=2x/2x-1 | | 4j+18-19j=-28 | | y=4(x+2)-3 | | 2/5(d-10)-2/3(d+6) | | 110+4x+10=180 | | -n+7-n+4n-3=-6 | | y=(x+3)-2 | | y=4(x-2)-3 | | x^2/3-1/64=0 | | y=4x(x-3)-4x | | -(-27z-7)-29z=28+(10z-16)-15 | | f(x)=.5(x-1) |